2021
DOI: 10.1038/s41598-021-93449-5
|View full text |Cite
|
Sign up to set email alerts
|

Elevated resting heart rate as a predictor of inflammation and cardiovascular risk in healthy obese individuals

Abstract: The role of leukocyte inflammatory markers and toll like receptors (TLRs)2/4 in pathologies associated with elevated resting heart rate (RHR) levels in healthy obese (HO) individuals is not well elucidated. Herein, we investigated the relationship of RHR with expression of leukocyte-inflammatory markers and TLRs in HO individuals. 58-obese and 57-lean participants with no history of a major medical condition, were recruited in this study. In HO individuals, the elevated-RHR correlated positively with diastolic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…First, the study was conducted on relatively young and healthy patients who underwent numerous types of lower extremity surgeries. However, since resting HR tends to be slow in young and healthy populations, [38,39] the strength of this study was the co-administration of an NCD, which prevented DEX-induced bradycardia. In addition, when only lower extremity surgery was included, the surgical position, method of anesthesia, and hemodynamic changes were relatively consistent.…”
Section: Discussionmentioning
confidence: 99%
“…First, the study was conducted on relatively young and healthy patients who underwent numerous types of lower extremity surgeries. However, since resting HR tends to be slow in young and healthy populations, [38,39] the strength of this study was the co-administration of an NCD, which prevented DEX-induced bradycardia. In addition, when only lower extremity surgery was included, the surgical position, method of anesthesia, and hemodynamic changes were relatively consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic and excessive consumption of a high‐calorie diet is believed to increase sympathetic tone [27]. Our previous studies demonstrated that CBS suppressed the activation of the SNS, decreased plasma NE concentration, and increased plasma ACH concentration in rats with HFD‐induced obesity [25].…”
Section: Discussionmentioning
confidence: 99%
“…Spearman correlation and multivariable regression analysis were performed to determine associations between different variables. As has been previously described [ 44 , 46 ], in all analyses, a p < 0.05 was considered significant. Standard multivariable linear regression by the Enter method was used; variables that significantly correlated with dectin-1 were selected as predictor variables and were entered simultaneously to generate the model.…”
Section: Methodsmentioning
confidence: 99%